Converting physical spaces into learning spaces: Integrating universal design and universal design for learning - Khurana, Aashna (Frontiers in Education, 2022)
The term ‘Universal Design for Learning (UDL)’ is derived from ‘Universal Design (UD)’, which is commonly used in the field of architecture, and focuses on proactive designing of infrastructure that is accessible to all the users, regardless of their abilities. When the universal design approach is implemented in education, it focuses on making the curriculum, instruction, materials, and assessments accessible for all the learners, but does not mention anything about the classroom and school infrastructure. This raises a question: is UDL framework forgetting its origin from UD by not recognizing the importance of school infrastructure, where all the learning happens? A way to approach this question is to think of school infrastructure as a learning resource that provides enriching learning experiences to learners, and not merely a brick-and-mortar structure that houses instruction. The school building comprises various physical spaces such as classrooms, corridors, playgrounds, staircases, etc. that can be transformed into learning spaces to promote subconscious learning in learners and ensure a school-wide implementation of UDL. Transforming school spaces would ensure learners equitable, inclusive, and accessible environments that reduce barriers to their learning. This would require transforming physical spaces (UD) into learning spaces (UDL), identifying different elements in each learning space to maximize their learning value and accessibility to school infrastructure. The chapter aims to provide a framework to design inclusive learning spaces by deriving insights from work of various groups of architects in India, Ireland, and the United States that have explored the relationship between physical spaces and UDL.